2017
DOI: 10.1111/1751-7915.12716
|View full text |Cite
|
Sign up to set email alerts
|

Caboxamycin biosynthesis pathway and identification of novel benzoxazoles produced by cross‐talk in Streptomyces sp. NTK 937

Abstract: Summary Streptomyces sp. NTK937, producer of benzoxazole antibiotic caboxamycin, produces in addition a methyl ester derivative, O‐methylcaboxamycin. Caboxamycin cluster, comprising one regulatory and nine structural genes, has been delimited, and each gene has been individually inactivated to demonstrate its role in the biosynthetic process. The O‐methyltransferase potentially responsible for O‐methylcaboxamycin synthesis would reside outside this cluster. Five of the genes, cbxR, cbxA, cbxB, cbxD and cbxE, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(63 citation statements)
references
References 39 publications
2
57
0
1
Order By: Relevance
“…sp. NTK 937), have been identified (Figure c) . Sequence analysis failed to identify any homologue to the enzymes in RiPPs or NRPs or an N‐type ATP pyrophosphohydrolase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…sp. NTK 937), have been identified (Figure c) . Sequence analysis failed to identify any homologue to the enzymes in RiPPs or NRPs or an N‐type ATP pyrophosphohydrolase.…”
Section: Introductionmentioning
confidence: 99%
“…This amide is then rearranged by the intramolecular attack of a hydroxyl and ring closure catalyzed by BomN (putative amidohydrolase) (Figure d). Since the gene clusters for nataxazole and caboxamycin all contain the homologue of the bomN amidohydrolase, the synthesis of the benzoxazole is expected to be the same in each case …”
Section: Introductionmentioning
confidence: 99%
“…We also sought to improve mutasynthesis yields by ectopic expression of regulatory gene cbxR in the strain ΔcbxA/ΔentC. However, production levels did not increase accordingly as in prior uses of cbxR [13], possibly due to the lack of cbxA , which might contain the effecting region for CbxR, given the structural organization of the biosynthetic cluster.
Fig. 6Schematic representation of the biosynthetic origin of compounds 1 – 19
…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, upon gene replacement of the salicylate synthase cbxA , a third compound was observed, 3′-hydroxycaboxamycin ( 3 ) (Fig. 1b), stemming from the cross-talk between the caboxamycin biosynthesis pathway and 2,3-dihydroxybenzoate (DHB) generated in the biosynthetic pathway for the siderophore enterobactin [13]. This phenomenon, together with our previous studies of the nataxazole biosynthetic cluster, where we identified cross-talk between the nataxazole and coelibactin biosynthesis pathways that led to biosynthesis of benzoxazole UK-1 [7, 8], sparked our interest for the generation of novel benzoxazoles exploring the biocombinatorial potential of these family of compounds.
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…The resulting dry residue was dissolved in methanol:DMSO (1:1) to perform UPLC and LC-MS analyses as described elsewhere [91,92]. …”
Section: Methodsmentioning
confidence: 99%